Conceptual Analysis of the Role of General Practitioners in Primary Health Care in Indonesia - Syifa Najla Izdihar; Azkiya Alika Putri Ahmudi (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2025)
ABSTRACT This study aims to provide a comprehensive conceptual analysis of the role of general practitioners (GPs) in Indonesia’s primary healthcare system amid ongoing health reforms under the National Health Insurance (JKN). Using a qualitative descriptive research design through a systematic literature review, data were collected from peer-reviewed journals, government reports, and academic publications focusing on the functions, challenges, and transformative potential of GPs. The analysis involved thematic identification, data reduction, conceptual categorization, and inductive interpretation to synthesize insights from current empirical and theoretical works. The findings reveal that GPs occupy a central position as gatekeepers of healthcare access, yet their role remains constrained by structural issues such as unequal workforce distribution, administrative burden, and limited professional autonomy. Emerging reforms—such as the Spesialis Kedokteran Keluarga Layanan Primer (Sp.KKLP) program and the GENOGRAM model—reflect a paradigm shift toward preventive, family-centered, and interdisciplinary healthcare. Interprofessional collaboration and digital system integration are identified as crucial enablers of quality improvement, though challenges persist in resource and infrastructure readiness. The study concludes that optimizing the GP’s role requires systemic reforms combining professional education, equitable workforce policies, and technology integration. Conceptually, the research enriches the understanding of primary care governance and highlights the importance of GPs as agents of transformation in achieving equitable and sustainable health systems in Indonesia. Keywords: General practitioners, primary healthcare, Indonesia, health system reform, qualitative study.